2019
DOI: 10.1007/s00374-019-01371-w
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of the autochthonous microbial soil community after amendment of cattle manure or its digestate

Abstract: In the last two decades, a change in land use has taken place in Europe. Manures that used to be applied to agricultural soils are now used in biogas reactors, and instead, digestate is applied. Here, we simulated soil amendment with either fresh or anaerobically digested cattle manure. The aim was to investigate the resilience of the resident microbiota and detect differences in the microbial biomass and activity after fertilizer amendment. Furthermore, the physiological community profile and the role of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…In another study, Barduca et al (2020) found anaerobic digestates to increase fungal activity while not changing microbial biomass. Also, no harmful effects have been observed on soil organisms after nine days (Johansen et al, 2013) or after one month of its application (Podmirseg et al, 2019). However, Westphal et al (2016) found only a minimal impact of anaerobic digestion on nematode, bacterial and fungi communities in soil one month after application of digestates.…”
Section: Tablementioning
confidence: 98%
See 1 more Smart Citation
“…In another study, Barduca et al (2020) found anaerobic digestates to increase fungal activity while not changing microbial biomass. Also, no harmful effects have been observed on soil organisms after nine days (Johansen et al, 2013) or after one month of its application (Podmirseg et al, 2019). However, Westphal et al (2016) found only a minimal impact of anaerobic digestion on nematode, bacterial and fungi communities in soil one month after application of digestates.…”
Section: Tablementioning
confidence: 98%
“…Within the soil food web, microorganisms and soil fauna (micro-, meso-and macrofauna) have a dominant role in shredding, transforming and decomposing soil organic matter (Brussaard, 2012;de Vries et al, 2013;Frouz, 2018). As such, soil organisms drive nutrient cycling (Osler and Sommerkorn, 2007), including N fixation (Singh et al, 2016), plant nutrient and water uptake (Geisseler et al, 2010), plant productivity (Van Der Heijden et al, 2008) and pathogen and antibiotic resistance (Chen et al, 2017;Podmirseg et al, 2019).…”
Section: The Relevance Of Soil Biodiversity and The Impact Of Intensive Farming Systemsmentioning
confidence: 99%
“…Gram-negative bacteria predominated the cultivable microbiota in frass-amended soil with highest CFU counts of up to 10 5 in soil treated with frass from a FV diet. High microbial load and dominance of coliforms in frass shifted to lower CFU numbers and predominantly gram-negative bacteria in the frass-soil mix, indicating that the autochthonous soil microbiota outcompeted allochthonous microorganisms introduced with frass [49][50][51].…”
Section: Assessment Of Microbial Load In Frass and Frass-amended Soilsmentioning
confidence: 99%
“…(2) these changes are primarily due to the physicochemical properties of the organic matrix rather than to newly introduced microorganisms, which are easily and rapidly outcompeted by members of the autochthonous soil microbiota (Podmirseg et al 2019). Don et al (2017) named this process as the "home-field advantage."…”
Section: Bacterial Compositional Responses To Soil Incorporation Of Solid Anaerobic Digestatementioning
confidence: 99%